2018
DOI: 10.5217/ir.2018.00041
|View full text |Cite
|
Sign up to set email alerts
|

IBD2020 global forum: results of an international patient survey on quality of care

Abstract: Background/AimsIBD2020 is a global forum for standards of care in inflammatory bowel disease (IBD). The aim of the IBD2020 survey was to identify and describe variations in quality care of IBD.MethodsPatients with IBD from Finland, Italy, France, Canada, Germany, UK, Spain and Sweden were surveyed during 2013 to 2014, covering: disease characteristics; impact on life and work; organization and perceived quality of care.ResultsSeven thousand five hundred and seven patients participated (median age, 39 years [ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…In a survey conducted by the IBD2020 global forum, 2 of the factors significantly associated with perceived excellent or very good quality of care were consultation length and the quality of specialist communication. 13 It has also been suggested that there is an unmet need for tools to aid discussion and align treatment goals. 6 In this global survey, the number one resource that physicians felt could most improve relationships with patients was an online tool or smartphone application to better monitor and track patient activities and symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a survey conducted by the IBD2020 global forum, 2 of the factors significantly associated with perceived excellent or very good quality of care were consultation length and the quality of specialist communication. 13 It has also been suggested that there is an unmet need for tools to aid discussion and align treatment goals. 6 In this global survey, the number one resource that physicians felt could most improve relationships with patients was an online tool or smartphone application to better monitor and track patient activities and symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The UC Narrative was composed of 2 related global surveys that separately examined the perspectives of patients and physicians across a range of countries. Although most IBD-related surveys encompass patients with UC and patients with Crohn disease, 13-15 these surveys were specific to UC. The UC Narrative survey questions explored aspects of living with UC, including day-to-day disease impact, disease management, goal-setting, and communication between patients and physicians.…”
Section: Introductionmentioning
confidence: 99%
“…Outcome measures involve traditional health care outcomes like hospitalisation, surgery and corticosteroid exposure, but patient-reported outcome and experience are also important as they reflect patient perspective on the quality of care. Despite various efforts to standardise structures, processes and outcomes [1][2][3][4][5][6][7][8] , and due to high variability at local, national and international levels, there are still no clear definitions or outcome measures available to establish quality of care standards for IBD patients that are applicable in all contexts and all countries.…”
Section: Introductionmentioning
confidence: 99%
“…The considerable psychosocial impact of IBD on education, careers, social and intimate well-being is well-documented in quality of life studies 15 16. Furthermore, patient surveys have drawn attention to concerns around delays in diagnosis, timeliness of review and treatment, access to appropriate inpatient facilities, coordination and continuity of care 17. The surveys also highlight needs relating to patients’ understanding about their condition, available treatment options and involvement in shared decision-making.…”
Section: Introductionmentioning
confidence: 99%